The Effect of Biochar and Cow Manual Fertilizer on Nutrition Upport and Production of Sweet Corn (Zea Mays L.) - Moh Khafid Nasrullah; Akbar Rafsanjani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The demand for sweet corn is increasing every year, one of the efforts to increase the production of sweet corn is to utilize suboptimal land such as post-PETI land. The purpose of the study was to examine the application of biochar and cow manure to nutrient uptake and the yield of sweet corn crops. This research was carried out in the experimental garden of the Faculty of Agriculture. This study is a factorial experiment arranged in a complete randomized design (RAL) with biochar and cow manure treatment. The first factor is biochar which consists of four dose levels, namely without biochar, biochar 6 tons / ha, 12 tons / ha and 18 tons / ha. The second factor is the application of manure with four dose levels, namely without manure, 20 tons / ha, 40 tons / ha and 60 tons / ha of manure each repeated 3 times, so that there are 48 experimental units. The results showed that pemberian pupuk cowshed as much as 60 tons / hectare and biochar as much as 18 tons / hectare can increase N absorption by 16.7%. The provision of cow shed p upuk as much as 40 tons / hectare and biochar as much as 18 tons / hectare can increase P and K absorption by 32.57% and 39.13%, respectively. The provision of cowshed p upuk as much as 20 tons / hectare and without biochar can increase Ca uptake by 3.74%. Hasil of sweet corn plants ranges from 0.3 to 1.67 tons / ha due to the application of manure and biochar.